Efficacy and safety of amphotericin B colloidal dispersion compared with those of amphotericin B deoxycholate suspension for treatment of disseminated murine cryptococcosis. - Hostetler, J S (1992)
The efficacy and safety of amphotericin B colloidal dispersion (ABCD) were compared with those of amphotericin B deoxycholate suspension (ABDS) (Fungizone) in a murine model of disseminated cryptococcosis. Mice were treated intravenously with either ABDS at 0.2, 0.8, or 3.2 mg/kg of body weight per dose or ABCD at 0.8, 3.2, 6.4, 12.8, or 19.2 mg/kg dose three times per week for 2 weeks. Excluding mice treated with ABDS at 3.2 mg/kg, which was acutely lethal in 100% of mice, and ABCD at 19.2 mg/kg, which also resulted in two early deaths, the survival of ABCD- and ABDS-treated groups was prolonged over survival of controls (P < or = 0.05). Survival of ABCD (3.2 mg/kg)-treated mice was improved over that of ABDS (0.2 mg/kg)-treated mice (P < 0.05); however, comparisons of mice given all other dosages of ABCD with mice given sublethal dosages of ABDS did not demonstrate differences in survival. Comparative fungal burdens in organs showed a decrease in liver (P < 0.05) and spleen (P < 0.05) burdens for ABCD with the 19.2-mg/kg therapy versus those with ABDS with the 0.8-mg/kg therapy and liver burdens for ABCD with the 12.8-mg/kg therapy versus ABDS with the 0.8-mg/kg therapy (P < 0.05). There was no difference in organ burdens between therapy with ABCD at 0.8 mg/kg and ABDS at 0.8 mg/kg. These data show that the efficacy of ABCD is equal to that of ABDS on a milligram-per-kilogram basis for murine disseminated cryptococcosis. Because of its decreased toxicity, greater efficacy with ABCD could be achieved through doses fourfold higher than the 100% lethal dose for ABDS. Thus, ABCD shows promise as an effective but less toxic alternative to ABDS for the treatment of disseminated cryptococcosis.